Air conditioning and refrigeration engineering - Wang, Shan K.; Lavan, Zalman ;Norton, Paul (Unites States of America : CRC Press, 2000)
An air conditioning system consists of components and equipment arranged in sequential order to control and maintain an indoor environment. The goal is to provide a healthy and comfortable climate with acceptable air quality while being energy efficient and cost effective. Air Conditioning and Refrigeration Engineering covers all types of systems from institutional and commercial to residential. The book supplies the basics of design, from selecting the optimum system and equipment to preparing the drawings and specifications. It discusses the four phases of preparing a project: gathering information, developing alternatives, evaluating alternatives, and selling the best solution. In addition, the author breaks down the responsibilities of the engineer, design documents, computer aided design, and government codes and standards.
Chapter 1. Introduction -- Chapter 2. Psychometrics -- Chapter 3. Air-Conditioning Processes and Cycles -- Chapter 4. Refrigeration Cycles -- Chapter 5. Outdoor Design Conditions and Indoor Design Criteria -- Chapter 6. Load Calculations -- Chapter 7. Air Handling Units and Packaged Unit -- Chapter 8. Refrigeration Components and Evaporative Coolers -- Chapter 9. Water Systems -- Chapter 10. Heating systems -- Chapter 11. Refrigeration Systems -- Chapter 12. Thermal Storage Systems -- Chapter 13. Air System Basics -- Chapter 14. Absorption Systems -- Chapter 15. Air-Conditioning systems and selection -- Chapter 16. Desiccant Dehumidification and Air-Conditioning.
First issue in paperback 2019.
Includes index.
Keywords: REFRIGERATION AND REFRIGERATING MACHINERY